Exploring the Role of Mindfulness in University Students’ Academic Well-being: Mediating Role of Emotional Resilience - Rohollah Saranjam; Saba Rasouli Amlashi (Iranian Journal of Educational Research)
Objective: This study aims to explore the role of mindfulness in enhancing the academic well-being of university students, with a focus on the mediating role of emotional resilience. Understanding how mindfulness and resilience interact can inform strategies for improving students' academic experiences. Methods: A cross-sectional survey design was employed, involving 300 university students aged 18-25 from various disciplines. Data were collected using the Five Facet Mindfulness Questionnaire (FFMQ), the Connor-Davidson Resilience Scale (CD-RISC), and the Student Well-being Questionnaire (SWQ). Pearson correlation analysis assessed the relationships among mindfulness, emotional resilience, and academic well-being. Structural Equation Modeling (SEM) was conducted to evaluate the mediating role of emotional resilience, using bootstrapping methods to test indirect effects. Results: The results indicated a significant positive correlation between mindfulness and academic well-being (r = 0.47, p < 0.001), as well as between mindfulness and emotional resilience (r = 0.56, p < 0.001). SEM analysis showed that emotional resilience partially mediated the relationship between mindfulness and academic well-being, with a significant indirect effect (β = 0.26, 95% CI = [0.15, 0.38]). The model demonstrated a good fit (CFI = 0.93, RMSEA = 0.06). Conclusions: Mindfulness positively influences academic well-being among university students, and this effect is partly mediated by emotional resilience. These findings suggest that interventions aimed at fostering both mindfulness and resilience may be effective in supporting students' academic success. Future research should consider longitudinal designs to further validate these relationships and assess the long-term impacts of mindfulness practices on academic outcomes.